The first eagle - Hillerman, Tony (Hillerman, Tony. Leaphorn & Chee novel., 1998)
The plague that decimated Europe in the 14th century appears to have returned in the high, dry land of the American Southwest. But detectives, Jim Chee and Joe Leaphorn, discover an even deadlier killer. The victims include not only police but also scientists hunting the key to the dread disease.